PHILOSOPHICAL MEANING ELEMENTS OF WAYANG KULIT LEMAH BALI PERFOMANCE ART - I Putu Ardiyasa; Widya Puspita Sati (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Puppet art has many types, one of which is Wayang (puppet) Lemah as a sacred performance that is used as an accompaniment to a yad ceremony. As the name implies, Wayang Lemah should be staged during the day and in line with the yad accompanied, but if the ceremony takes place at night, still use the Wayang Lemah Show, because its main function is accompanying the Panca yad namely: Manusa yadnya, Pitra yadnya, Dewa yadnya, Bhuta yadnya and yad receipt. This study seeks to examine more deeply the elements of Wayang Lemah Show from philosophical aspects. The data of this study were obtained through observation, interviews with five Puppeteer masters and looking for additional data through library studies. This research shows that every element (people, puppets, gamelan and supporting property) has interconnected philosophical meanings.Keywords: Philosophy, Wayang, Wayang Lemah